Networked control systems with sampling interval adaptation - Godoy, Eduardo Paciência [UNESP]; Porto, Arthur José Vieira (My University, 2018)
Networked control systems (NCSs) are distributed control system where the sensors, actuators and controllers are physically separated and connected through communication networks. The challenge in the development of NCS is to overcome the effects of the network delays, packet losses and message sampling intervals on the NCS performance and stability. This chapter describes the design and evaluation of NCSs with online adaptation of the sampling interval. The idea is centered on a PID controller that online adapts the NCSs sampling interval, reducing the network load while maintaining the NCS performance. The performance and robustness of the online adaptation scheme are analyzed for different NCS configurations used on a CAN-based NCS research platform, showing significant results in the CAN network load reduction. Experimental results led to the conclusion that the developed online adaptation scheme is reliable for application to NCS, providing an acceptable performance for the NCS even in the worst-case scenario investigated.
Keywords: CAN protocol; Network load; PID controller; Sampling interval